2021
DOI: 10.1167/tvst.10.9.16
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Severity of Visual Field Damage From Retinal Nerve Fiber Layer Thickness Measurements With Artificial Intelligence

Abstract: The purpose of this study was to assess the accuracy of artificial neural networks (ANN) in estimating the severity of mean deviation (MD) from peripapillary retinal nerve fiber layer (RNFL) thickness measurements derived from optical coherence tomography (OCT).Methods: Models were trained using 1796 pairs of visual field and OCT measurements from 1796 eyes to estimate visual field MD from RNFL data. Multivariable linear regression, random forest regressor, support vector regressor, and 1D convolutional neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…However, methods predicting global VF metrics have generally outperformed those attempting to predict location‐specific VF thresholds from OCT data 17,19,23 . Qualitative topographic comparisons between OCT‐derived retinal nerve fibre layer (RNFL) and ganglion cell‐inner plexiform layer (GCIPL) thicknesses and VF thresholds have reported global agreement between abnormal structure and function in up to 88.7% of patients with early glaucoma 17,23 Moreover, various deep learning methods have been applied to RNFL and GCIPL data to enable prediction of summary VF metrics such as mean deviation and VF index, with moderate to strong correlations reported between predicted and actual VF parameters 24–26 . These indicate promising utility of these methods in predicting global functional results from OCT.…”
Section: Introductionmentioning
confidence: 99%
“…However, methods predicting global VF metrics have generally outperformed those attempting to predict location‐specific VF thresholds from OCT data 17,19,23 . Qualitative topographic comparisons between OCT‐derived retinal nerve fibre layer (RNFL) and ganglion cell‐inner plexiform layer (GCIPL) thicknesses and VF thresholds have reported global agreement between abnormal structure and function in up to 88.7% of patients with early glaucoma 17,23 Moreover, various deep learning methods have been applied to RNFL and GCIPL data to enable prediction of summary VF metrics such as mean deviation and VF index, with moderate to strong correlations reported between predicted and actual VF parameters 24–26 . These indicate promising utility of these methods in predicting global functional results from OCT.…”
Section: Introductionmentioning
confidence: 99%
“…We also observed that estimation performance in the external test set was better compared with the internal test set, which could be attributed to differences in the spatial distribution of focal severities in the two test sets. Strengths of our study include the use of a standardized, stratified approach for dataset construction, the There has been continued interest in the development and evaluation of models for the estimation VF loss in glaucoma from structural measurements of the retina [9][10][11][12][13][14]27,28 with reported MAEs in the range of 2-5 dB [11][12][13][14] for VF MD estimation. In most previous studies, comparisons with other approaches were largely limited to linear regression 9,11,12,28 or SVMs.…”
Section: Discussionmentioning
confidence: 99%
“…Strengths of our study include the use of a standardized, stratified approach for dataset construction, the There has been continued interest in the development and evaluation of models for the estimation VF loss in glaucoma from structural measurements of the retina [9][10][11][12][13][14]27,28 with reported MAEs in the range of 2-5 dB [11][12][13][14] for VF MD estimation. In most previous studies, comparisons with other approaches were largely limited to linear regression 9,11,12,28 or SVMs. 11,28 As data-driven ML models networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Along with detection, if an AI algorithm was able to measure the RNFL thickness accurately, the diagnosis would be made more effective, as that is the most common parameter used for glaucoma diagnosis. 12 13 …”
Section: F Uture a Pplications And ...mentioning
confidence: 99%